THE ROLE OF TEACHER BELIEFS IN IMPLEMENTING INNOVATIVE PEDAGOGIES - Viviana Lisma Lestari; Suwarsito Suwarsito (Penelitian dan Pengembangan Ilmu, 2024)
This research aims to explore the role of teachers' beliefs about technology in the integration of innovative pedagogy in the classroom. Using a systematic literature review approach, this research analyzes literature related to teachers' views about technology, the factors that influence their beliefs, and its impact on the implementation of technology-based pedagogy. The main findings indicate that teachers' positive beliefs towards technology encourage the adoption of innovative pedagogy, while negative beliefs limit the application of technology in teaching. The implications of this research point to the importance of training and supporting policies to optimize the use of technology in education.